(untitled) (Journal of Philosophy Culture and Political Science, 2022)
The publication analyzes approaches to understanding media management in world science. In particular, the differences in the interpretation of media management by English-speaking science (management of a media enterprise from the business perspective in a competitive environment) and within the framework of the scientific discourse of the CIS countries (microeconomics – the level of the enterprise, macroeconomics – the state level) are clearly demonstrated. In this regard, the use of the term “state media management” is justified, author offers it’s definition. Also, in a schematic form, the main milestones of the periodization of media management research in the far abroad, in the USSR and post-Soviet countries are summarized. The article reveals the main circle of problems that are in the field of attention of researchers of the state media management sphere; it shows examples of the main challenges and risks arising from the ever-accelerating development of information and communication technologies. The possibilities and tools of the state in terms of supporting the media sphere are considered: e.g., benefits and loans for media enterprises, subsidies for auxiliary companies serving the media sphere (for example, for postal and forwarding companies), financing of socially significant media, improving compliance with intellectual property rights, etc. Prospects for further research are outlined, and the connection between state media management and education is shown, both at the level of the state order for the training of media managers, and in connection with the approval of core competencies, the presence of which is important for this profession. Key words: media management, state media management, media sphere management, information technologies, mass media, mass media.